Obsessive-compulsive disorder : symptoms, therapy and clinical challenges - Nelson, Jeffrey L. (Psychiatry - theory, applications and treatments, 2022)
"Obsessive-compulsive disorder (OCD), which is characterized by distressing intrusive thoughts and repetitive, time-consuming, task-oriented actions intended to counter these thoughts and reduce anxiety, represents a serious psychiatric condition and cause of disability worldwide. This book consists of five chapters that provide details on the effects of OCD and strategies for reducing its negative impact. Chapter One provides a general overview of OCD, including its neurochemical basis and treatment approaches. Chapter Two explores some of the nuisances present in working with individuals with OCD within the context of obsessive and compulsive content that may require additive elements to be considered in treatment. Chapter Three discusses the diagnostic criteria, clinical aspects, and current treatment approaches of pediatric acute-onset neuropsychiatric syndrome and pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections. Chapter Four describes the effects of the COVID-19 pandemic on children and adolescents with OCD. Lastly, Chapter Five explains the role that religion takes in certain presentations of OCD and informs clinicians how to differentiate between standard religious practices and compulsive behaviors"--